Penggunaan Media Power Point Dalam Meningkatkan Motivasi Belajar Siswa di MA Darul Mahfudz - Susanto , Heri (CV. ITTC INDONESIA, 2024)
This article discusses the optimization of PowerPoint use in increasing student motivation at MA Darul Mahfudz in 2023. The research was conducted to determine the extent to which the effectiveness of PowerPoint use in the learning process can increase student motivation. The research method used was a quantitative method with a survey approach. The results showed that optimal use of PowerPoint in the learning process can increase student motivation. This is shown from the increase in the average student score after the implementation of PowerPoint use in the learning process. This article recommends that teachers make more use of technologies like PowerPoint in the learning process to increase student motivation.